2016
DOI: 10.1039/c6tc00611f
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and pressure-induced phase transitions in the niccolite-type formate framework of [H3N(CH3)4NH3][Mn2(HCOO)6]

Abstract: [H3N(CH3)4NH3][Mn2(HCOO)6] shows ferroelectric and magnetic order below 350 and 9 K, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 57 publications
6
45
0
Order By: Relevance
“…They were also predicted theoretically for ethylammonium and guanidinium analogues . Multiferroic properties were also discovered for two iron(II)‐iron(III) mixed valence frameworks of general formula [cat][Fe II Fe III (HCOO) 6 ] (cat = dimethylammonium or diethylammonium) and [NH 3 (CH 2 ) 4 NH 3 ][Mn(HCOO) 6 ] …”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…They were also predicted theoretically for ethylammonium and guanidinium analogues . Multiferroic properties were also discovered for two iron(II)‐iron(III) mixed valence frameworks of general formula [cat][Fe II Fe III (HCOO) 6 ] (cat = dimethylammonium or diethylammonium) and [NH 3 (CH 2 ) 4 NH 3 ][Mn(HCOO) 6 ] …”
Section: Introductionmentioning
confidence: 85%
“…The known formates have been extensively studied in a broad temperature range, and these studies showed that majority of them undergo phase transitions associated with orientational ordering of organic cations located in the cavities of the framework . Pressure is another thermodynamic parameter that can help to better understand structure–property relationship in this class of compounds . For instance, it has been shown that application of pressure may lead to enhancement of ferroelectric properties or its suppression .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, an investigation of behavior of MOFs in response to this external stimulus is necessary, especially from the application point of view. Up to date, a few papers reported high pressure studies of chiral, perovskite and niccolite metal formate frameworks. These studies revealed presence of pressure‐induced transformations and negative linear compressibility for some compounds.…”
Section: Introductionmentioning
confidence: 99%